EFFECTIVENESS OF NSAIDS FOR PAIN MANAGEMENT IN PERIODONTAL SURGERY - Antoaneta Mlachkova; Velitchka Dosseva-Panova (Peytchinski Publishing, 2023)
Introduction: The perception of pain is subjective and many factors may affect its power and duration in various oral surgical procedures. An effective treatment suggests a certain volume of knowledge and skills of dental practitioners. A combination of non-pharmacological and pharmacological agents is often used to relieve the pain. There is evidence that non-steroidal anti-inflammatory drugs (NSAIDs) are effective in treating acute pain. Hypotheses suggest that NSAIDs have analgesic and anti-inflammatory effects by reducing the synthesis of arachidonic acid's metabolites - prostaglandins (PGE2, PGI2), thromboxane (TxA2, TxB2) which are responsible for the occurrence of both - inflammation and pain. With the hyperalgesia initiated by PGE2 and bradykinin, we can explain the presence of postoperative pain because it reduces the pain threshold and increases susceptibility to available threshold inducements. Aim: To evaluate the effectiveness of postoperative NSAID administration in order to prevent the production of inflammatory components induced by the surgical treatment. Material and methods: The study included 15 patients who received surgical therapy. The selective COX-2 inhibitor of the new class Aulin® and the non-selective COX-2 inhibitor Ibuprofen® were taken from the patients as systemic administration postoperatively for a period of 3 days. The VRS-4 scale was used to assess the pain. Results: The assessment of the mean values for the degree of pain did not show statistically significant differences in the inhibition of pain for the two drugs in the three postsurgical days. Conclusion: In the absence of a significant difference between the two drugs - Aulin® and Ibuprofen®, we may confirm that according to our study they are both sufficiently effective in controlling postoperative pain in surgical periodontal procedures.